Early recurrence of atrial fibrillation after catheter ablation with left atrial fibrosis identified at cardiac magnetic resonance by late gadolinium enhancement. (August 2016) - Totaro, Antonio; Casavecchia, Graziapia; Gravina, Matteo; Ieva, Riccardo; Santoro, Francesco; Grimaldi, Massimo; Pellegrino, Pier Luigi; Macarini, Luca; Di Biase, Matteo; Brunetti, Natale Daniele
In patients with atrial fibrillation (AF), extensive atrial tissue fibrosis identified by delayed enhancement magnetic resonance imaging has been associated with early recurrence of AF after catheter ablation. We present a case of a patient with extensive atrial fibrosis and AF recurrence. The study of late gadolinium enhancement with cardiac magnetic resonance imaging in patients with AF could be a valuable noninvasive tool for the selection of patients suitable for successful catheter ablation.